Management of Fashion Design Upgrading Program in BBPVP Semarang (Lembaga Pengembangan Kinerja Dosen, 2025)
BBPVP Semarang is a leading center for Fashion Technology and includes a subunit dedicated to Instructor Development for both government and private sectors, particularly in the field of Fashion Technology with a focus on Fashion Design Programs. It is the only work unit that offers an Upgrading Program in Fashion Design. The purpose of the upgrading program is to enhance knowledge in Fashion Design, which evolves annually based on trend forecasting and aligns with the needs of the business and industrial sectors. This study aims to describe and analyze the management of the upgrading program implemented by the Balai Besar Pengembangan Vokasi dan Produktivitas (BBPVP) Semarang, focusing on the planning, implementation, and evaluation phases. This research employs a qualitative approach using a case study method. Data collection techniques include interviews, observations, and documentation. The research uses source triangulation, involving 2 echelon 3 and 4 officials, 2 administrative staff members from Intala, 2 instructors, and 20 upgrading participants. Data were analyzed using an interactive analysis model, which includes data collection, data presentation, and drawing conclusions. The results show that the planning of the upgrading program at BBPVP Semarang involves identifying training needs, determining the training program, system, location, schedule, and methods, participant recruitment and selection, preparing human resources, training facilities, training schedule, and organization. The implementation of the upgrading program includes preparation, execution, assessment, responsibilities, and the issuance of training and competency certificates. The evaluation of the upgrading program includes aspects such as training materials, instructors, facilities and infrastructure, training materials, job readiness, meals, and boarding. In conclusion, the program management is running effectively and involves all elements, receiving positive appreciation from the participants.